DESAIN ETL DENGAN CONTOH KASUS PERGURUAN TINGGI - Spits Warnars (Jurnal Informatika, 2009)
Data Warehouse for higher education as a paradigm for helping high management in order to make an effective and efficient strategic decisions based on reliable and trusted reports which is produced from Data Warehouse itself. Data Warehouse is not a software, hardware or tool but Data Warehouse is an environment where the transactional database is modelled in other view for decision making purposes. ETL (Extraction, Transformation and Loading) is a bridge to build Data Warehouse and transform data from transactional database. In every fact and dimension table will be inserted with fields which represent the construction merge loading as an ETL (Extraction, Transformation and Loading) extraction. ETL needs an ETL table and ETL process where ETL table as table connectivity between tables in OLTP database and tables in Data Warehouse and ETL process will transform data from table in OLTP database into Data Warehouse table based on ETL table. The extraction process will be run with a table database as differentiate ETL process and an ETL algorithm which will be run automatically in idle transactional process, along with daily transactional database backup when the information system are not used.